Relationship between brand experience, brand image, perceived value and customer engagement: a study of starbucks in China - Li, Sijia (2020)
This research takes Starbucks as an example to study the relationship between brand experience, brand image, perceived value and customer engagement. Using a sample of 291 valid questionnaires collected in China, regression analyses were employed to test the hypotheses. The main findings of the study indicate that: (1) brand experience is positively related to perceived value; (2) brand image is positively related to customer engagement; (3) perceived value partially mediates the relationship between brand experience and customer engagement; (4) perceived value partially mediates the relationship between brand experience and customer engagement.